Pengaruh E-Commerce dan Financial Technology Terhadap Ketimpangan Pendapatan Di Indonesia - Dwiki Dimas Pradipta; Apridar Apridar (Kajian Ekonomi dan Akuntansi Terapan, 2024)
This research aims to analyze the influence of e-commerce and financial technology on income inequality in Indonesia. This research uses panel data from 10 provinces in Indonesia in the 2018-2022 period. This research uses a panel random effect model (REM) regression approach with a GLS (generalized least square) estimation tool. The estimation results from this research show that e-commerce has a negative and significant effect on income inequality in Indonesia. Meanwhile, financial technology has a positive and significant effect on income inequality in Indonesia. It is hoped that the results of this research can be used as consideration for the government in making policies in an effort to reduce income inequality in Indonesia.